Nucleophilic Substitution Reaction of Imidazole with Various 2-Bromo-1-arylethanone Derivatives: A Computational Study - Fatma Oğuz Erdoğan; Taner Erdoğan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Inthis study, it was intended to investigate the reactions between imidazole and2-bromo-1-arylethanones such as 2-bromoacetophenone,2-bromo-1-(4-chlorophenyl)ethan-1-one,2-bromo-1-(2,4-dichlorophenyl)ethan-1-one and 2-bromo-1-(furan-2-yl)ethan-1-one,computationally. In the study, some Density Functional Theory (DFT)calculations have been performed on the chemical species involved in theinvestigated chemical reactions. DFT calculations have been performed at DFTB3LYP (Becke, three-parameter, Lee-Yang-Parr) level of theory using 6-31G(d),6-31G(d,p), 6-311G(d,p) and 6-311+G(2d,p) basis sets. Single Point Energy (SPE)calculations, geometry optimizations, vibrational analysis, Frontier MolecularOrbital (FMO) calculations, global reactivity descriptor determinations,Molecular Electrostatic Potential (MEP) map calculations and estimation of thenuclear magnetic shielding tensors have been carried out at the same levels oftheory. In 1H-NMR calculations, CSGT (Continuous Set of GaugeTransformations) and GIAO (Gauge-Independent Atomic Orbital) models were usedand experimental data have been compared with the computationally obtaineddata.